Cluster analysis of motor coordination and health-related fitness in preschool children: population classification and variable contribution based on principal component analysis - Chen, Xiaoxiao; Zhao, Deqiang; Zhang, Aoyu; Wang, Chunmiao; He, Jin; Chen, Jiaxin; Hu, Haixia; Tang, Xiaoni; Zhang, Aiying; Xiao, Han; Zhang, Yanfeng (Frontiers in Public Health, 2025)
BackgroundThe preschool period is critical for children’s motor development and neural maturation. Fundamental motor skill development during this stage directly influences the nervous system’s growth. Motor coordination ability serves as the foundation for children’s physical fitness, health, and motor performance.ObjectiveThis study investigates the relationship between motor coordination and health-related fitness in preschool children, analyzing the extent of motor coordination’s impact on physical fitness. Through principal component analysis (PCA) and cluster analysis, differences in motor coordination and fitness performance across child populations are identified, providing theoretical support for optimizing health promotion strategies.MethodsParticipants included 358 preschool children from a kindergarten in Weifang, Shandong, China., including demographic data such as parental education, socioeconomic background, and habitual physical activity participation collected via parent questionnaires to provide contextual information Motor coordination was assessed using the Movement Assessment Battery for Children-2 (MABC-2), while fitness tests (e.g., standing long jump, tennis throw, 10-meter shuttle run) were standardized into Z-scores. Statistical analyses included Pearson correlation, hierarchical regression, PCA, and cluster analysis. PCA component retention was based on eigenvalues >1 and scree plot inspection, while cluster validity was confirmed using the elbow method and silhouette coefficients.ResultsMotor coordination showed significant positive correlations with flexibility, strength, agility, and endurance. Hierarchical regression confirmed motor coordination’s independent and significant influence on fitness outcomes, particularly in standing long jump and shuttle run. BMI exhibited a weak negative correlation with motor coordination. PCA revealed two principal components (Dim1: 31.7% variance, dominated by running and jumping; Dim2: 16.1% variance, emphasizing flexibility and tennis throw). Cluster analysis categorized children into three groups: “Comprehensive Excellence,” “Agility Specialization,” and “Basic Skill Needs.”ConclusionMotor coordination plays a pivotal role in preschool children’s fitness development, particularly in agility and strength. PCA and cluster analysis highlighted distinct group differences, supported by validated retention and validation procedures, underscoring the need for targeted interventions to enhance motor coordination and overall health.